The clinical and immunological basis of early food introduction in food allergy prevention - Nuyttens, L.; De Vlieger, L.; Diels, M.; Schrijvers, R.; Bullens, D. M. A. (Frontiers in Allergy, 2023)
IgE-mediated food allergy has an estimated prevalence of 6%–10% in developed countries. Allergen avoidance has long been the main focus in the prevention of food allergy and late solid food introduction after 6–12 months of age was recommended in high-risk infants. However, the rising prevalence of food allergy despite delayed exposure to allergens and the observations that IgE-mediated sensitization to food products could even occur before the introduction of solid foods resulted in a shift towards early solid food introduction as an attempt to prevent IgE-mediated food allergy. Since then, many trials focused on the clinical outcome of early allergen introduction and overall seem to point to a protective effect on the development of IgE-mediated food allergies. For non-IgE-mediated diseases of food allergy, evidence of early food introduction seems less clear. Moreover, data on the underlying immunological processes in early food introduction is lacking. The goal of this review is to summarize the available data of immunological changes in early food introduction to prevent IgE and non-IgE mediated food allergy.